Evaluation Of The Effectiveness The Use Of Capcut-Based Video Learning Media In Improving Student Understanding And Engagement In Physical Education And Sports - Supriyani Sirregar, Epi; Purnama Sari, Ika; Fahruzy Nasution, Alwi; Purwandari, Elce; Muliyadi Daulay, Sehat (Universitas Pahlawan Tuanku Tambusai, 2025)
The use of technology in education has grown rapidly, with video-based learning media becoming one of the effective tools in improving the quality and effectiveness of teaching. The CapCut application, known as a video editing platform, offers features that can be used to develop interesting and informative learning videos. This study focuses on the use of CapCut in creating video learning media for Physical Education and Sports subjects, with the aim of evaluating its effectiveness in improving student understanding and engagement. The purpose of this study was to evaluate the effectiveness of using CapCut-based video learning media in improving student understanding and engagement in Physical Education and Sports subjects. This study aims to explore how videos made with CapCut can affect the way students understand the concepts of sports and physical activity and the extent to which this media can increase student motivation and engagement in the learning process. This study uses a mixed research method, namely a combination of quantitative and qualitative. The results of the study showed that the use of CapCut-based video learning media significantly improved students' understanding of Physical Education and Sports materials. Videos developed with CapCut were able to present information visually and auditorily that clarified complex concepts. In addition, students showed increased engagement and motivation in the learning process, as reflected in class activities and their responses to video materials. Educators also reported that this media facilitated the delivery of materials and increased interaction with students. This study concludes that the use of CapCut in developing video learning media has a significant positive impact on students' understanding and engagement in Physical Education and Sports. CapCut provides a tool that allows educators to create engaging and interactive learning videos, which in turn improves the quality of learning and student motivation. Therefore, the application of this technology can be an effective solution to improve the learning process in schools. Further research is recommended to explore other aspects of the use of digital media in education and to identify best practices in its implementation